Open Access: An Evaulation of its Impact, Obstacles, and Advancements - Miles, Rachel A. (My University, 2016)
Access to research results is imperative in today’s robust digital age, yet access is often prevented by publisher paywalls. Open Access (OA) is the simple idea that all research should be free for all to access, use, and build upon. This paper will focus on three critical areas of the OA landscape: its impact on scholarship and the public, the obstacles to be overcome, and its advancements. The impact of OA actions and initiatives has been difficult to quantify, but the growing number of studies on OA have shown mostly overwhelmingly positive results. Cultural norms within academia, such as the reliance on the journal Impact Factor (IF) to assess the quality of individual research articles, have impeded the progress of OA. Conversely, federal mandates and institutional policies have supported the OA movement by requiring that scholarly publications be deposited into institutional or subject repositories immediately following publication. As information professionals, library and information science (LIS) professionals have a responsibility as practitioners, authors, and editors to support OA and encourage other academics to do the same.
Citation: Miles, Rachel. (2016). Open Access: An Evaulation of its Impact, Obstacles, and Advancements. Bibliotekar, 58: (1-2). http://bds.rs/wordpress/?p=1762
Keywords: Open Access; scholarly publishing; self-archiving; copyright; scholarly communication; digital scholarship